Correction: Author Correction: Integrated genomic analyses of de novo pathways underlying atypical meningiomas - Akdes Serin Harmancı (Nature Portfolio, 2018)
Nature Communications 8: Article number: 14433 (2017) Published online 14 February 2017; Updated 20 April 2018 In this Article, a subset of the H3K27ac ChIP-seq data (15 benign meningiomas and 2 dura samples (Sample IDs: MN-297, MN-288, MN-292, MN-163, MN-1037, MN-105, MN-201, MN-249, MN-191, MN-1066, MN-169, MN-291, MN-24, MN-79, MN-1044, CONTROL1, CONTROL2) was reported previously in a publication by the corresponding author1.